2018
DOI: 10.1021/acsami.8b10111
|View full text |Cite
|
Sign up to set email alerts
|

Mesoporous ZnMn2O4 Microtubules Derived from a Biomorphic Strategy for High-Performance Lithium/Sodium Ion Batteries

Abstract: ZnMn2O4 microtubules (ZMO-MTs) with a mesoporous structure are fabricated by a novel yet effective biomorphic approach employing cotton fiber as a biotemplate. The fabricated ZMO-MT has approximately an inner diameter of 8.5 μm and wall thickness of 1.5 μm. Further, the sample of ZMO-MT displays a large specific surface area of 48.5 m2 g–1. When evaluated as a negative material for Li-ion batteries, ZMO-MT demonstrates an improved cyclic performance with discharge capacities of 750.4 and 535.2 mA h g–1 after 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(22 citation statements)
references
References 65 publications
0
22
0
Order By: Relevance
“…In Figure 4c, the high resolution Zn 2p XPS spectrum exhibits two characteristic peaks at 1020.9 and 1044.0 eV, corresponding to the spin orbits of Zn 2p 3/2 and Zn 2p 1/2 of ZnSe, respectively. [ 36,37 ] In Figure 4d, two obvious peaks of Se 3d are located at 54.1 and 54.8 eV, correlated with the spin orbits of Se 3d 5/2 and Se 3d 3/2 of ZnSe, respectively. [ 38,39 ] There is a small peak at around 56.1 eV, caused by excessive selenium powder during the selenization process.…”
Section: Resultsmentioning
confidence: 99%
“…In Figure 4c, the high resolution Zn 2p XPS spectrum exhibits two characteristic peaks at 1020.9 and 1044.0 eV, corresponding to the spin orbits of Zn 2p 3/2 and Zn 2p 1/2 of ZnSe, respectively. [ 36,37 ] In Figure 4d, two obvious peaks of Se 3d are located at 54.1 and 54.8 eV, correlated with the spin orbits of Se 3d 5/2 and Se 3d 3/2 of ZnSe, respectively. [ 38,39 ] There is a small peak at around 56.1 eV, caused by excessive selenium powder during the selenization process.…”
Section: Resultsmentioning
confidence: 99%
“…This can be ascribed to the carbon layer, which covers the active sites of the active materials. 39,40 In subsequent cycles, two anodic peaks at ~1.2 V (Mn 0 to Mn 2+ ) and ~1.5 V (Zn 0 to Zn 2+ ) and one cathodic peak at ~0.5 V (Mn 2+ to Mn 0 and Zn 2+ to Zn 0 ) can be observed, indicating the occurrence of conversion reactions. 19 In Figure 6b&c, the cathodic peak of the ZMO shifts to lower potential and the intensities of redox peaks decrease upon cycling.…”
Section: Electrochemical Measurementsmentioning
confidence: 97%
“…Zinc manganate­(ZnMnO)-based electrode materials have been well-recognized for their electrocatalytic redox characteristics and the nanoscale structure, which facilitates a fast electron transfer process that is advantageous for electrochemical applications. Very recently, Li et al reported ZnMnO/graphene for the electrochemical detection of hydrogen peroxide (H 2 O 2 ) with good catalytic activity . Subsequently, Li et al explored a ZnMnO-based electrocatalyst for the determination of H 2 O 2 .…”
Section: Introductionmentioning
confidence: 99%